Quercus candicans (Fagaceae) is not a Quercus but a Roldana (Asteraceae) - Valencia-A., Susana; Coombes, Allen; Villaseñor, José Luis (Phytotaxa, 2018)
A revision of type material of Quercus candicans at the Herbarium of the Real Jardín Botánico de Madrid (MA), as well as the original description revealed misplacement in the genus Quercus (Fagaceae). The type of Q. candicans clearly corresponds to Roldana lineolata (Asteraceae). A detailed study of types and protologues of the synonyms previously placed under Q. candicans by Muller and Trelease, indicate the oldest valid name for this species is Q. calophylla, which the material referred to this species must now be called. The taxonomic confusion is clarified and a new combination in Roldana, based on Q. candicans is proposed.